DNA Barcode Analysis of Dendrobium sp. Based On rbcL Sequence - Dwinianti, Edia Fitri; Durotun Ainiyah; Yusfi Afidah; Mukhamad Su'udi (Jurnal Biologi Tropis, 2025)
Morphological characterization of Dendrobium orchids needs to be supported by the utilization of DNA barcoding as a faster and more accurate approach. This study aims to identify the rbcL marker as a potential barcode for Dendrobium sp. collected from Jenggawah, Jember. The isolation of Dendrobium sp. genomic DNA was performed using the CTAB method, and the isolated DNA was amplified using PCR. The PCR products were used for sequencing analysis, and the sequence data were analyzed using several bioinformatics programs namely BLAST, ClustalX 2.1, and MEGA11. The results showed that the Dendrobium sp. sequence had a high level of homology with Calanthe alpina (MN192480.1), with a genetic similarity of 99.82%. The sequence analysis results of rbcL in Dendrobium sp. showed low genetic variation, which made rbcL less effective for use as a molecular marker at the species level. The rbcL barcode showed universal results for Dendrobium sp., so it needs to be supported by molecular identification using other markers such as matK and ITS for a more effective identification method in distinguishing between species.